Kondisi Sosial Ekonomi Keluarga Sebagai Faktor Penentu Keberhasilan Pembagunan ( Suatu Studi di Kecamatan Malalayang ) - Renyaan, Lidya; Pangkey, Masje Silija; Rorong, Arie Junus (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Social condition is a state in a country at a given time. Economics is defined as the use ofmoney, power, precious time (Poerwodarminta, 1990). The purpose of the socio-economicconditions in this study were the circumstances or background of a family related to education,employment, income and socio-economic keluarga.Kondisi in this study were standing or positionof a person or family in the community with regard to the level of education, level income propertyor facility ownership and type of residence. The successful development of an achievement ofdevelopment that has been planned in order to create a more advanced state of society and modern.In this case the development is the pioneer of the government, both central and local pemeritah. Aregion is successful in doing development if the people in that area is no longer living under thepoverty line, capable of creating jobs for others, and on the mark with good economic turnaround.The method used in this research is descriptive and explanatory survey using a quantitativeapproach. As for the variables in this study are: socio-economic condition of the family and thesuccess of the development. By Arikunto (2002) argues that "the entire population is a subject ofresearch". the sample is part of the number and characteristics of which is owned by thepopulation (Sugiyono, 2002). Sample location (sub sample) chosen by purposive sampling of 3(three) villages, namely: Malalayang One, Stone City, and Winangun Two. The number ofrespondents 99 based on samples determined through a formula Yamane (Rahkmat, 1991). Resultsof the analysis for 0893 is a positive correlation between socio-economic conditions of the familyand the success of development. Furthermore, the coefficient of determination of 0.79 means thatthe influence / contribution of socio-economic conditions of the family to the success ofdevelopment, obtained by 89.3% and the remaining 10.7% is influenced by other factors. Movingon from the research results mentioned above, it can be said that the socio-economic condition ofthe family has significance in terms of achieving the success of developmentKeywords: Social-Economic Conditions Family, Development Success